Teatro experimental do negro: trajetória e reflexões - Nascimento, Abdias do (Estudos Avançados, 2004)
THIS ESSAY examines the career of the Teatro Experimental do Negro (Black People's Experimental Theater), founded in Rio de Janeiro in 1944, and its long-standing proposal to work for the social enhancement of black people in Brazil through education, culture and art.